Stability of Butter Using Spray Dried Sweet Lime Peel (SLP) Powder - Zahra Maqbool; Hafiza Saima Tahir; Muhammad Tahir Nadeem; Rabia Shabir Ahmad; Adeela Yasmin; Waseem Khalid; Turky Omar Asar; Mayada Ahmad Al-Sameen (International Journal of Food Properties, 2023)
The current study was designed to evaluate the effects of sweet lime peel powder (SLPP) on the quality and stability of butter at different storage intervals. Butter is a high-fat food containing trace amounts of water, minerals, and vitamins. Limetta Citrus Risso contains polyphenols, antioxidants, antimicrobial compounds, minerals, and vitamins. Physicochemical analysis (hunter color (L*, a*, and b*) and pH), quality tests (TBARS value and peroxide value), antioxidant activity (DPPH and total phenolic contents), microbiological analysis, and sensory evaluation of butter enriched with SLPP were performed to observe the changes on different treatments at storage intervals with vacuum and aerobic packaging. The butter was treated with 1.5%, 3%, 4.5%, and 6% sweet lime peel powder (SLPP). The variations in TBARS and POV were observed significantly in butter during different treatments, storage periods, and packaging. The results showed that color was changed significantly concerning different treatments, storage periods, and packaging. The L* and b* values were observed to be highest in aerobic packaging, whereas the a* value was increased in vacuum packaging. The antioxidants (DPPH, and TPC) varied significantly in both types of packaging on different treatments at storage intervals. High DPPH and phenolic contents were noticed in the 6% SLPP sample, while lower values were noted in the control sample. The negligible variations were analyzed in appearance, taste, color, odor, and overall acceptability.